Afro-brazilian religions: adaptations and challenges (Ágora Journal, 2025)
Afro-brazilian religions, such as Candomblé and Umbanda, are pillars of Brazil's cultural identity. Despite their relevance, they face a contemporary paradox: while gaining institutional recognition, they continue to suffer from persistent religious intolerance, a reflection of structural racism. In this context, this article analyzes how the resistance strategies of these traditions have been reconfigured, shifting from historical practices of syncretism to a political struggle for rights and visibility. The objective is to investigate the impact of recent public policies—notably their recognition as cultural heritage by IPHAN (Brazil's National Historical and Artistic Heritage Institute) and the implementation of Law 10.639/03—on the valorization and preservation of these religious practices. Grounded in Clifford Geertz's Interpretive Anthropology, the qualitative methodology involves a literature review and a documentary analysis of legislation and institutional reports. The study concludes that although legal advancements represent a fundamental achievement, they are insufficient to overcome the barriers of prejudice. The analysis reveals that terreiros (Afro-Brazilian places of worship) are consolidating their role as central spaces not only for worship but also for political resistance and the strengthening of Afro-descendant identity in Brazilian society.
Keywords: Afro-Brazilian religions; religious intolerance; cultural resistance; syncretism; Afro-descendant identity.